Effect of spermatozoa viability, culture receptacle, incubation, and intracytoplasmic sperm injection on vitro production of cattle embryoa using epididymal spermatozoa - Raseona, Andrea Motswetla (My University, 2022)
In an event of an unexpected death, injury, or inability of a bull to serve, spermatozoa can be harvested from the epididymides to enable the propagation of valuable germplasm from genetically superior males. Recovering bull spermatozoa from the epididymis of dead breeders presents the last opportunity to use the gametes and therefore, the need for the most efficient preservation and utilization of the recovered spermatozoa is paramount. One of the unique ways of preserving the male genetic material of cattle is the use of assisted reproductive technologies. The present study focused primarily on the production of in vitro cattle embryos using epididymal spermatozoa by firstly seeking the effective spermatozoa extender and preservation method, and secondly by assessing the effects of culture receptacles and incubation methods following intracytoplasmic sperm injection. In a series of experiments, ejaculated and epididymal spermatozoa were collected, chilled, cryopreserved, and used for in vitro embryo production. The viability of chilled bovine spermatozoa recovered from the epididymis stored at 5 °C for 24 h and diluted with Triladyl® or modified Ham’s F10 was assessed in the first experiment. The short-term preserved (120 h at 5 °C) ejaculated spermatozoa demonstrated a higher motility rate than epididymal sperm, however, epididymal spermatozoa harvested immediately after bull slaughter, extended with Triladyl® was found to have a higher motility rate (P < 0.05) than spermatozoa harvested 24 h post chilling of the epididymides at 5 °C diluted in modified Ham’s F10 culture media. A significant decline in viability was also demonstrated after 72 h of chilling at 5 °C with the least percentage of live cells detected with modified Ham’s F10 extended epididymal spermatozoa harvested 24 h post-mortem. Furthermore, less than 10% of acrosome defects were demonstrated across all the spermatozoa samples. It was concluded that refrigeration of epididymides at 5 °C for 24 h before the recovery of spermatozoa cells was able to sustain good spermatozoa motility when Triladyl® extender was used. The viability of frozen-thawed bull semen collected from the bull’s ejaculate and cauda epididymis was also evaluated. Similar to the observations on spermatozoa chilling in the first experiment, ejaculated spermatozoa had a higher post-thaw motility rate (P < 0.05) than epididymal sperm. However, no significant difference in post-thaw motility rate was demonstrated amongst epididymal spermatozoa recovered immediately and 24 h post-mortem (P > 0.05). The post-thaw percentage of acrosome defects, as well as the live cells, was found to be similar for both ejaculated and epididymal sperm. It was concluded that cooling of epididymides at 5 °C for 24 h before the recovery of spermatozoa cells was efficient in preserving post-thaw spermatozoa quality. In the third experiment, the success rates of in vitro embryo production using epididymal bull sperm, French semen straws as culture receptacle, and alternative incubation method was evaluated. The experiment was carried out as a completely randomised design arranged in a 3 x 2 x 2 factorial. The results demonstrated that short-term preserved (120 h at 5 °C) ejaculated spermatozoa produced a higher percentage of in vitro embryos compared to epididymal spermatozoa. However, no significant difference (P > 0.05), in blastocyst development was demonstrated between epididymal spermatozoa retrieved immediately and after 24 h post-mortem, extended in either Triladyl® or modified Ham’s F10, chilled for either 24 or 48 h. Additionally, no significant difference was demonstrated when comparing individual spermatozoa samples using French semen straws as culture receptacles, incubated in the goat doe vagina, versus a standard 5% CO2 incubator. It was concluded that in vitro embryos up to 8 days of development, cultured in French semen straws and incubated in the goat doe vagina, can be produced after fertilization with epididymal bull spermatozoa recovered immediately or after refrigeration of the epididymides at 5 °C for 24 h. Lastly, the study investigated the effect of using French semen straws as embryo culture receptacle and goat doe vagina as an alternative incubator, on in vitro embryo production following intracytoplasmic sperm injection with epididymal spermatozoa. The injected oocytes with epididymal spermatozoa recovered after bull slaughtering or after 24 hours post-mortem, cultured inside French semen straws or micro-droplets, had no difference in embryonic development rates (P > 0.05). Furthermore, when both the standard CO2 incubator and the goat doe vagina were used, no difference in embryo development stages was identified (P > 0.05), with the exception of the cleavage stage where the injected oocytes incubated in goat doe vagina showed lower rates (P < 0.05) as compared to those incubated in the standard CO2 incubator. It was concluded that fertilization and blastocyst development can be accomplished through intracytoplasmic sperm injection with cryopreserved bull epididymal spermatozoa recovered immediately or 24 h post-mortem, using French semen straws as culture receptacles and goat doe vagina as an alternative incubator.
PhD (Animal Science)
Department of Animal Science
Keywords: Epididymal spermatozoa; UCTD; Triladyl®; Ham’s F10; Cryopreservation; Intracytoplasmic sperm injection (ICS; Goat doe vagina.; In vitro embryo production